2022
DOI: 10.1093/annweh/wxac056
|View full text |Cite
|
Sign up to set email alerts
|

Detection of SARS-CoV-2 in Air and on Surfaces in Rooms of Infected Nursing Home Residents

Abstract: There is an ongoing debate on airborne transmission of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) as a risk factor for infection. In this study, the level of SARS-CoV-2 in air and on surfaces of SARS-CoV-2 infected nursing home residents was assessed to gain insight in potential transmission routes. During outbreaks, air samples were collected using three different active and one passive air sampling technique in rooms of infected patients. Oropharyngeal swabs (OPS) of the residents and dry s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 40 publications
0
16
2
Order By: Relevance
“…This is in contrast with findings from previous outbreak investigations conducted at mink farms and nursing homes, where similar sampling technologies were applied [1,22]. In these studies, several air samples collected in COVID-19 infected mink farms, and a high percentage of both air and surface swab samples collected in rooms in nursing homes with SARS-CoV-2 positive patients [1,22]. A previous study in London also found limited evidence of SARS-CoV-2 contamination in school environments [18].…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…This is in contrast with findings from previous outbreak investigations conducted at mink farms and nursing homes, where similar sampling technologies were applied [1,22]. In these studies, several air samples collected in COVID-19 infected mink farms, and a high percentage of both air and surface swab samples collected in rooms in nursing homes with SARS-CoV-2 positive patients [1,22]. A previous study in London also found limited evidence of SARS-CoV-2 contamination in school environments [18].…”
Section: Discussioncontrasting
confidence: 80%
“…Although we found evidence of SARS-CoV-2 transmission within secondary schools, the lack of detectable SARS-CoV-2 RNA in collected air and surface samples suggests that major environmental contamination was uncommon in schools under the prevailing conditions at the time of the study. This is in contrast with findings from previous outbreak investigations conducted at mink farms and nursing homes, where similar sampling technologies were applied [1,22]. In these studies, several air samples collected in COVID-19 infected mink farms, and a high percentage of both air and surface swab samples collected in rooms in nursing homes with SARS-CoV-2 positive patients [1,22].…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Current nucleic acid detection methods require the nucleic acids to be suspended in a liquid buffer. [ 21,38 ] However, airborne viral RNA or DNA is present in airborne viral particles at concentrations much lower than the limit of detection of current detection methods. [ 30,39,40 ] Thus, airborne viral particles must be collected and enriched from the air during sample collection.…”
Section: Device Requirements For Wearable Airborne Viral Nucleic Acid...mentioning
confidence: 99%
“…During this stage, a biorecognition element binds the target of interest. Current biorecognition strategies for nucleic acids commonly center on the hybridization of the target sequence to a short complementary primer or probe such as in polymerase chain reaction (PCR) or clustered regularly interspaced short palindromic repeats (CRISPR), [ 21,38 ] respectively. The goal is to have the biorecognition element bind with high specificity and sensitivity to the target analyte.…”
Section: Device Requirements For Wearable Airborne Viral Nucleic Acid...mentioning
confidence: 99%